The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.4236/ojpm.2015.56033
|View full text |Cite
|
Sign up to set email alerts
|

Sickle Cell Gene Transmission: Do Public Servants in Tamale, Ghana Have the Right Knowledge and Attitude to Curb It?

Abstract: Introduction: Sickle cell disease (SCD) is exerting enormous public health and economic burden on many countries. To reduce these effects, the World Health Organization is urging countries, especially those in Africa, to increase public awareness of this disease. This study accessed whether public servants in Tamale, Ghana possess adequate knowledge and positive attitude towards SCD. Method: A total of 320 public servants within the Tamale Metropolis were invited to complete a questionnaire in a cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…This is presumably because students had easy access to tools like the Internet while they were in school and were also taught about hereditary illnesses. This finding was consistent with previous studies [25,26] that reported that most participants learned about SCD from media and school. This suggests that schools and the media can be effective institutions and platforms for educating people about SCD.…”
Section: Plos Onesupporting
confidence: 93%
“…This is presumably because students had easy access to tools like the Internet while they were in school and were also taught about hereditary illnesses. This finding was consistent with previous studies [25,26] that reported that most participants learned about SCD from media and school. This suggests that schools and the media can be effective institutions and platforms for educating people about SCD.…”
Section: Plos Onesupporting
confidence: 93%
“…Almost half (65%) of the participants had poor knowledge, moderate knowledge (30%) and excellent knowledge (5%) of SCD. This is consistent with previous study in Ghana that demonstrated low knowledge of SCD [22]. Similar poor knowledge about SCD was reported by a study in Eastern and Western Uganda [23].…”
Section: Poorsupporting
confidence: 93%
“…Regarding concerns about difficulty finding a life partner, findings are in line with those of a study assessing knowledge and attitude toward SCD among public servants in Tamale, Ghana. A majority of the respondents, 78% (n = 230) would abandon marriage intentions if premarital screening had shown that they and their current spouses had sickle cell traits (Ameade et al, 2015). In another study that focused on religious and cultural aspects of SCD to identify beliefs and attitudes relevant to public health interventions in Ghana, families/individuals with SCD, health care providers, religious leaders, and marriage counselors were consistent in describing the social norm that would-be couples who both have sickle cell S trait, let alone SCD, should be discouraged to proceed to marry in Ghanaian societies (Dennis-Antwi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%